Maximal medical therapy for chronic rhinosinusitis: a survey of otolaryngology consultants in the United Kingdom. Issue 2 (4th October 2012) - Sylvester, Deborah Claire; Carr, Simon; Nix, Paul
<x xml:space="preserve">Abstract</x> Background The management of chronic rhinosinusitis is based on a trial of "maximal medical therapy" before surgery is considered. Ear‐Nose‐Throat (ENT) UK consultant members were surveyed to determine the role and variability of UK‐wide practices. Methods A survey was posted to all ENT UK consultant members (n = 603). This assessed the frequency of prescription, duration, and type of oral antibiotics, steroids, and antihistamines for chronic rhinosinusitis. Results A total of 158 questionnaires (26.3%) were returned. Of these, 61% were primarily rhinologists. The use of decongestants, antifungals, and immunotherapy was generally limited. Oral antibiotics were often used, with clarithromycin of <5 weeks duration being the preferred choice. Sixty‐one percent of consultants always prescribe a steroid spray, most commonly mometasone furoate (75%). Conclusion Although most respondents use triple therapy of oral antibiotics, steroid nasal spray, and saline douching to some extent, "maximal medical therapy" for chronic rhinosinusitis seems to vary greatly among consultants and frequently does not reflect recent guidelines.